Practical-Problematic Features of the Application of the Rule of Exception to the Admissibility of Evidence (pt. 6 of Article 1.93 of CC of the Republic of Lithuania) - Kaklys, Karolis (Socialiniai tyrimai, 2022)
Article 1.93 (pt. 2) of the Civil Code of the Republic of Lithuania there is an established imperative that non-compliance with the form required by law deprives the parties of the process of the right, when there is a dispute regarding the conclusion of the transaction or the fact of its execution, to rely on the testimony of witnesses to prove this fact. In this scientific article, an empirical study was conducted, the purpose of which is to evaluate Article 1.93 (pt. 6) of the CC of the Republic of Lithuania the practical-problematic features of the application of the rule of exception to the admissibility of evidence, i.e. when, after applying the exception, the court is not guided by Article 1.93 (pt. 2) of the CC of the Republic of Lithuania established imperative. The research consists of six interrelated stages, during which the following scientific methods were applied: systematic analysis, document analysis, comparative analysis, logical-analytical, observation and generalization methods. The chosen research strategy and methodology determines the reliability of the research results and allows us to answer the hypothesis - is the jurisprudence formed by the Supreme Court of Lithuania sufficiently detailed and delineating clear boundaries for the courts of lower instances, applying Article 1.93 (pt. 6) of the CC of the Republic of Lithuania established exception to the admissibility of evidence and in order to avoid dual application of the legal norm. The research results are presented together with the conclusions, the essential conclusion is that - after the formation of a more detailed the highest court jurisprudence regarding the application of the rule of exception to the admissibility of evidence, Article 1.93 (pt. 2 and 6) of the CC of the Republic of Lithuania, the equality of persons would be ensured, more concreteness and stability would be created in civil relations, and this would significantly facilitate the resolution of disputes in the future.